(S)-lacosamide inhibition of CRMP2 phosphorylation reduces postoperative and neuropathic pain behaviors through distinct classes of sensory neurons identified by constellation pharmacology. Issue 7 (July 2016) - Moutal, Aubin; Chew, Lindsey A.; Yang, Xiaofang; Wang, Yue; Yeon, Seul Ki; Telemi, Edwin; Meroueh, Seeneen; Park, Ki Duk; Shrinivasan, Raghuraman; Gilbraith, Kerry B.; Qu, Chaoling; Xie, Jennifer Y.; et al.
Abstract : Abstract: Chronic pain affects the life of millions of people. Current treatments have deleterious side effects. We have advanced a strategy for targeting protein interactions which regulate the N-type voltage-gated calcium (CaV2.2) channel as an alternative to direct channel block. Peptides uncoupling CaV2.2 interactions with the axonal collapsin response mediator protein 2 (CRMP2) were antinociceptive without effects on memory, depression, and reward/addiction. A search for small molecules that could recapitulate uncoupling of the CaV2.2–CRMP2 interaction identified ( S )-lacosamide [( S )-LCM], the inactive enantiomer of the Food and Drug Administration–approved antiepileptic drug ( R )-lacosamide [( R )-LCM, Vimpat]. We show that ( S )-LCM, but not ( R )-LCM, inhibits CRMP2 phosphorylation by cyclin dependent kinase 5, a step necessary for driving CaV2.2 activity, in sensory neurons. ( S )-lacosamide inhibited depolarization-induced Ca 2+ influx with a low micromolar IC50 . Voltage-clamp electrophysiology experiments demonstrated a commensurate reduction in Ca 2+ currents in sensory neurons after an acute application of ( S )-LCM. Using constellation pharmacology, a recently described high content phenotypic screening platform for functional fingerprinting of neurons that uses subtype-selective pharmacological agents to elucidate cell-specific combinations (constellations) of key signaling proteins that define specific cell types, we investigated if ( S )-LCM preferentially acts on certain types of neurons. ( S )-lacosamide decreased the dorsal root ganglion neurons responding to mustard oil, and increased the number of cells responding to menthol. Finally, ( S )-LCM reversed thermal hypersensitivity and mechanical allodynia in a model of postoperative pain, and 2 models of neuropathic pain. Thus, using ( S )-LCM to inhibit CRMP2 phosphorylation is a novel and efficient strategy to treat pain, which works by targeting specific sensory neuron populations. Abstract : Supplemental Digital Content is Available in the Text.( S )-lacosamide blocks CRMP2 phosphorylation leading to reduced voltage-gated calcium activity. ( S )-lacosamide demonstrates antinociceptive efficacy through actions on distinct classes of sensory neurons identified by constellation pharmacology.